Sodankylä ionospheric tomography data set 2003–2014 - J. Norberg; L. Roininen; A. Kero; T. Raita; T. Ulich; M. Markkanen; L. Juusola; K. Kauristie (Geoscientific Instrumentation, Methods and Data Systems, 2016)
Sodankylä Geophysical Observatory has been operating a receiver network for ionospheric tomography and collecting the produced data since 2003. The collected data set consists of phase difference curves measured from COSMOS navigation satellites from the Russian Parus network (Wood and Perry, 1980) and tomographic electron density reconstructions obtained from these measurements. In this study vertical total electron content (VTEC) values are integrated from the reconstructed electron densities to make a qualitative and quantitative analysis to validate the long-term performance of the tomographic system. During the observation period, 2003–2014, there were three to five operational stations at the Fennoscandia sector. Altogether the analysis consists of around 66 000 overflights, but to ensure the quality of the reconstructions, the examination is limited to cases with descending (north to south) overflights and maximum elevation over 60°. These constraints limit the number of overflights to around 10 000. Based on this data set, one solar cycle of ionospheric VTEC estimates is constructed. The measurements are compared against the International Reference Ionosphere (IRI)-2012 model, F10.7 solar flux index and sunspot number data. Qualitatively the tomographic VTEC estimate corresponds to reference data very well, but the IRI-2012 model results are on average 40 % higher than that of the tomographic results.